Implementing health system improvement: resources and strategies for interprofessional teams. Issue 1 (27th January 2023) - Eljiz, Kathy; Greenfield, David; Hogden, Anne; Agaliotis, Maria; Taylor, Robyn; Siddiqui, Nazlee
Abstract : Health system improvement (HSI) is focused on systematic changes to organisational processes and practices to improve the efficient delivery of safe care and quality outcomes. Guidelines that specify how interprofessional teams conduct HSI and knowledge translation are needed. We address this urgent requirement providing health professional teams with resources and strategies to investigate, analyse and implement system-level improvements. HSI encompasses similar, yet different, inter-related activities across a continuum. The continuum spans three categories of activities, such as quality improvement, health management research and translational health management research. A HSI decision making guide and checklist, comprising six-steps, is presented that can be used to select and plan projects. This resource comprises six interconnected steps including, defining the activity, project outcome, aim, use of evidence, appropriate methodology and implementation plan. Each step has been developed focusing on an objective, actions and resources. HSI activities provide a foundation for interprofessional collaboration, allowing multiple professions to create, share and disseminate knowledge for improved healthcare. When planned and executed well, HSI projects assist clinical and corporate staff to make evidence-informed decisions and directions for the benefit of the service, organisation and sector.